2019
DOI: 10.1007/s00018-019-03024-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of mitochondrial dynamics affects behaviour and lifespan in Caenorhabditis elegans

Abstract: Mitochondria are essential components of eukaryotic cells, carrying out critical physiological processes that include energy production and calcium buffering. Consequently, mitochondrial dysfunction is associated with a range of human diseases. Fundamental to their function is the ability to transition through fission and fusion states, which is regulated by several GTPases. Here, we have developed new methods for the non-subjective quantification of mitochondrial morphology in muscle and neuronal cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 79 publications
(115 reference statements)
9
73
1
Order By: Relevance
“…A recent study investigating the effect of perturbing mitochondrial fission and fusion on C. elegans lifespan and health span showed that loss of fission decreased neuronal function and performance across several behavioral tests primarily during development (L4 stage) and in aged animals (day 7 and day 11 adults), but not during early adulthood (day 3 adults). Loss of fusion, however, produced more consistent and progressive neurological and behavioral defects all across development and adulthood (L4, day 3, day 7, and day 11 adults) [82]. Complementary findings from Rana et al showing lifespan extension in Drosophila only upon midlife induction of mitochondrial fission, not in early adulthood, and lifespan shortening with midlife upregulation of dMFN highlight that mitochondrial fission plays a key role in early development and around midlife [27].…”
Section: Mitochondrial Dynamics: Is Timing Key?mentioning
confidence: 78%
See 1 more Smart Citation
“…A recent study investigating the effect of perturbing mitochondrial fission and fusion on C. elegans lifespan and health span showed that loss of fission decreased neuronal function and performance across several behavioral tests primarily during development (L4 stage) and in aged animals (day 7 and day 11 adults), but not during early adulthood (day 3 adults). Loss of fusion, however, produced more consistent and progressive neurological and behavioral defects all across development and adulthood (L4, day 3, day 7, and day 11 adults) [82]. Complementary findings from Rana et al showing lifespan extension in Drosophila only upon midlife induction of mitochondrial fission, not in early adulthood, and lifespan shortening with midlife upregulation of dMFN highlight that mitochondrial fission plays a key role in early development and around midlife [27].…”
Section: Mitochondrial Dynamics: Is Timing Key?mentioning
confidence: 78%
“…Despite the requirement of fusion for lifespan‐extending interventions , most studies show that driving fusion or fission alone is not sufficient to increase lifespan and sometimes negatively affects health and longevity. Deletion of drp‐1 , fzo‐1 , or eat‐3 in C. elegans reduces median lifespan and induces motor and sensory impairments, yet pathologies associated with inhibiting one process can often be restored by inhibiting the other . Yeast cells deficient for fission and fusion ( dnm1 ; mgm1 double knockout, Table ) actually have healthy‐looking mitochondria with a wild‐type morphology, although these yeast do have a shortened lifespan .…”
Section: Introductionmentioning
confidence: 99%
“…Even though burrowing of nematodes in soil-like environments has been previously studied [48][49][50], only recently has it been used for evaluation of neuromuscular health in C. elegans [16,18,19,22,51]. These recent investigations employed agar as a medium for burrowing.…”
Section: Pluronic As a Novel Medium For C Elegans Burrowingmentioning
confidence: 99%
“…Since the original method was conceived [18], it has been applied to score muscular dystrophy mutants [16], and to probe calcium dysregulation and longevity outcomes due to physical exertion in the burrowing environment in these mutants [19]. Additionally, a burrowing assay has been used to assess mutants with defects in mitochondrial fission and fusion proteins [22]. Here, we have developed an improved burrowing method based on a thermoreversible Pluronic gel and expanded its application to diverse areas with novel findings.…”
Section: Burrowing Is a Sensitive Phenotyping Tool To Evaluate Neurommentioning
confidence: 99%
See 1 more Smart Citation